15N‐carnitine, a novel endogenous hyperpolarized MRI probe with long signal lifetime. Issue 4 (12th November 2020) - von Morze, Cornelius; Engelbach, John A.; Reed, Galen D.; Chen, Albert P.; Quirk, James D.; Blazey, Tyler; Mahar, Rohit; Malloy, Craig R.; Garbow, Joel R.; Merritt, Matthew E.
Abstract : Purpose: The purpose of this study was to investigate hyperpolarization and in vivo imaging of [ 15 N]carnitine, a novel endogenous MRI probe with long signal lifetime. Methods: L ‐[ 15 N]carnitine‐ d 9 was hyperpolarized by the method of dynamic nuclear polarization followed by rapid dissolution. The T1 signal lifetimes were estimated in aqueous solution and in vivo following intravenous injection in rats, using a custom‐built dual‐tuned 15 N/ 1 H RF coil at 4.7 T. 15 N chemical shift imaging and 15 N fast spin‐echo images of rat abdomen were acquired 3 minutes after [ 15 N]carnitine injection. Results: Estimated T1 times of [ 15 N]carnitine at 4.7 T were 210 seconds (in H2 O) and 160 seconds (in vivo), with an estimated polarization level of 10%. Remarkably, the [ 15 N]carnitine coherence was detectable in rat abdomen for 5 minutes after injection for the nonlocalized acquisition. No downstream metabolites were detected on localized or nonlocalized 15 N spectra. Diffuse liver enhancement was detected on 15 N fast spin‐echo imaging 3 minutes after injection, with mean hepatic SNR of 18 ± 5 at a spatial resolution of 4 × 4 mm. Conclusion: This study showed the feasibility of hyperpolarizing and imaging the biodistribution of HP [ 15 N]carnitine.